Workshop peningkatan spiritualitas istri yang cakap berdasarkan Amsal 31 : 10 - 31 bagi Ibu PW Jemaat GKI Syalom Pasifik Indah Klasis Porth Numbay: Workshop on enhancing the spirituality of a wife of noble character (Proverbs 31:10–31) for the Women’s Fellowship of the GKI Syalom Pasifik Indah Congregation, Porth Numbay Classis - Ruhulessin, Cleopatriza T. F. (Fakultas Peternakan Universitas Papua, 2025)
ABSTRACT Married women who serve as wives play a vital role in the family. While a wife’s roles and responsibilities cannot be equated with those of the husband as head of the household, they are equally important. A wife’s role in accompanying her husband becomes a source of motivation for the success of both husband and children, including in ministry. Becoming a wise wife is essential in both family and societal contexts. A wise wife not only manages the household well but also actively supports her husband’s work, contributes to children’s education, and safeguards family harmony. Therefore, members of the Women’s Fellowship need to recognize the importance of their role and strive to become wise wives for the good of the family and the community. This community service program (PkM) employed lecture and question–answer methods to enable the active participation of Women’s Fellowship members in developing understanding and theological implementation of the concept of a wise wife, which is reflected in sound spirituality. The importance of spirituality in a wife’s life cannot be understated. With mature spirituality, a wife can become a pillar of strength in the family, build effective communication, provide moral guidance, and strengthen family bonds. Consequently, women need to recognize the importance of cultivating spirituality within themselves to become wise wives who contribute to family well-being. Keywords: Workshop, Spirituality, Wife, Proverbs 31, Port Numbay Classis. ABSTRAK Perempuan yang sudah menikah dan menjadi seorang istri memiliki peranan yang sangat penting di dalam sebuah keluarga. Peran dan tanggung jawab seorang istri dalam keluarga memang tidak dapat disamakan dengan seorang suami sebagai kepala keluarga; namun peran dan tanggung jawab seorang istri dalam keluarga mempunyai arti yang sama pentingnya. Peran istri yaitu mendampingi suaminya akan menjadi motivasi tersendiri bagi keberhasilan suami dan anak-anak juga dalam pelayanan. Menjadi istri yang bijak adalah sebuah keharusan dalam konteks keluarga dan masyarakat. Istri yang bijak tidak hanya mampu mengelola rumah tangga dengan baik, tetapi juga berperan aktif dalam menopang kerja suami, pendidikan anak dan menjaga keharmonisan keluarga. Dengan demikian, ibu-ibu PW perlu menyadari pentingnya peran mereka dan berusaha untuk menjadi istri yang bijak demi kebaikan keluarga dan masyarakat. Pelaksanaan PkM ini menggunakan metode ceramah dan tanya jawab untuk memungkinkan partisipasi aktif ibu-ibu PW dalam pengembangan pemahaman dan implementasi teologis tentang istri yang bijak, yang akan terlihat pada spiritualitas yang baik. Pentingnya spiritualitas dalam kehidupan seorang istri tidak dapat dipandang sebelah mata. Dengan memiliki spiritualitas yang baik, seorang istri dapat menjadi pilar kekuatan dalam keluarga, membangun komunikasi yang efektif, memberikan panduan moral, dan memperkuat ikatan keluarga. Oleh karena itu, perempuan perlu menyadari pentingnya mengembangkan spiritualitas dalam diri mereka untuk menjadi istri yang bijak dan berkontribusi pada kesejahteraan keluarga. Kata Kunci : Workshop, Spiritualitas, Istri, Amsal 31, Klasis Port Numbay